The Effect of the Picture Exchange Communication System on Individuals with Autism Spectrum Disorder - Aslı Kanadlı; Derya Genç Tosun (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: The aim of this study was to examine the effect of the Picture Exchange Communication System (PECS) protocol in teaching individuals with moderate/severe autism spectrum disorder (ASD) the ability to initiate spontaneous communication and request food.Method: In the study, a single-subject research model, multiple probe design with across-participant was used. The participants of the study were three boys diagnosed with moderate/severe ASD attending a special education practice school. The independent variable of the study was the first three phases of the PECS protocol, and the dependent variable was the child's ability to initiate spontaneous communication and request food. The study included baseline, intervention, generalization and follow-up sessions.Results: The first three phases of the PECS protocol were found to be effective in children with moderate/severe ASD in learning the skill of requesting food. The children were able to maintain the food-requesting skill they learned one and three weeks after the last intervention session and were able to generalize this skill to different environments and people. Teachers who participated in the study as communication partners expressed positive opinions about the study.Discussion: The effectiveness findings of the study are consistent with other studies in the literature that examined the effect of PECS on the acquisition of requesting skills by individuals with ASD. The findings were discussed in comparison with the related literature and suggestions were made for future research and practice.